In vitro effectiveness of chemical fungicides against Curvularia eragrostidis (Henn) J. A. Mey, causal agent of leaf spot disease in pineapple (Scientia Agropecuaria, 2021)
Curvularia eragrostidis (Ascomycota: Dothideomycetes) was recently reported as the causal agent of Pineapple Leaf Spot disease (MD2 hybrid) in Central Pacific Mexico. Therefore, the effectiveness of five chemical fungicides (System Cu®, Tilt® 250 CE, Volley® 88OL, Tecto 60® and Mancozeb® 80WP) at four concentrations (1.0%, 0.5%, 0.25% and 0.125%) was evaluated through a doses response bioassay. The DGR of C. eragrostidis was 1.5 cm/day. The fungicides Volley® and Tilt® at the four evaluated concentrations did not allow the growth of C. eragrostidis. The lowest DGR for System Cu®, Mancozeb® 80WP and Tecto® 60 was found at the dose of 1% with 0.13, 0.0 and 0.39 cm / day, respectively. The %IMG for Volley® and Tilt® 250 CE were 100% at all evaluated doses. For System Cu®, Mancozeb® 80WP and Tecto® 60, the %IMG ranged from 65.2 (0.125%) - 78.2 (1.0%), 62.9 (0.125%) - 100.0 (1.0%) and 57.0 (0.125%) - 62.0% (1.0%), respectively. The Probit model suggested an LC50 of 0.025%, 0.067% and 0.076% for System Cu®, Mancozeb® 80WP and Tecto® 60, respectively. In conclusion, the fungicides Volley® and Tilt® are highly effective against C. eragrostidis; on the other hand, the EC50 for System Cu®, Mancozeb® 80WP and Tecto® 60 against C. eragrostidis are reported for the first time.
Keywords: Ananas comosus; chemical control; doses response bioassay; daily growth rate; mycelial growth inhibition percentage; mean lethal concentration